ANALYSIS OF THE ROLE OF MANAGEMENT IN THE PRIVATIZATION OF THE “PORT OF BELGRADE” AND THE COOPERATIVES IN VOJVODINA - Stanimir Djukić; Milan Brkljač; Dražen Jovanović (Ekonomika Poljoprivrede (1979))
The paper examines the role of management and the economic consequences during the purchase of state and cooperative enterprises (combines), and states that the consequences are enormous. Also, the paper discusses in more detail the privatization of cooperative combines (enterprises) in Vojvodina. That process began in its most extreme after the elections held in September 2000. In addition, the paper analyses the problem of construction land on the example of “Port of Belgrade”, i.e. the combination of crime, tycoons and politicians in the aforementioned privatization.